Case Report: Exploration of changes in serum immunoinflammation-related protein complexes of patients with metastatic breast cancer - Chen, Chang; Xu, Yali; Lai, Zhizhen; Li, Zhili; Sun, Qiang (Frontiers in Oncology, 2023)
Patients with advanced breast cancer are difficult to treat and have poor prognosis. At present, the commonly used methods to monitor the disease progression of breast cancer are imaging examinations such as breast ultrasound, mammography and peripheral blood tumor markers such as carcinoembryonic antigen (CEA) and carbohydrate antigen 15-3 (CA15-3). However, none of them can detect tumor progression at an early stage. Serum immunoinflammation-related protein complexes (IIRPCs) showed potential to indicate cancer progression. Therefore, we attempted to monitor the level of IIRPCs in peripheral blood of patients with metastatic breast cancer and compare it with patients' treatment and disease progression, and here we performed case reports of two of them.